Psychosocial needs of relatives of missing persons: Experiences and testimonies of women leaders of mexican collectives - Flores Morales, Rogelio; Márquez García, Liliana Paola (Revista Colombiana de Ciencias Sociales, 2026)
Introduction: The aime of this research is to identify, describe and systematize the psychosocial needs of relatives of people who are victims of forced or private disappearance, from the perspective of seven women leaders of collectives located in four states of the Mexican Republic with high rates of violence (Estado de México, Guerrero, Jalisco and Veracruz). Methodology: A qualitative study was carried out with a crosssectional, exploratory and descriptive design, through in-depth interviews. Results: The study highlights the urgency of strengthening comprehensive and multidisciplinary approaches that address the psychosocial dimensions of victims’ needs. At the same time, it highlights the importance of guaranteeing the safety and protection of family members in the search processes, as well as dignified and respectful treatment by institutions. Finally, it highlights the relevance of community participation and empathy in the regeneration of the social fabric and the construction of peace. Conclusions: The findings of this study can contribute to the improvement of public policies and programs that are more effective and sensitive to the needs of the families of missing persons in Mexico, contributing to their recovery and comprehensive well-being.